Low-cost base drag reduction technique - Asad Ullah, Mohammed; Khan, Sher Afghan; Asrar, Waqar; Sulaeman, Erwin (International Journal of Mechanical Engineering and Robotics Research, 2018)
A simple, low-cost, drag reduction device has been developed for applications in high-speed flows. This low-cost technology is expected to decrease fuel consumption (e.g., for high-speed vehicles such as rockets traveling from a highly over expanded flow at the sea level to a highly under expanded flow in outer space). Somewhere in between the over and the under expansion, the rocket experiences perfectly expanded flows. In this study, only over expanded and perfectly expanded flows have been considered. A single cylinder with a diameter of 2 mm is rotated clockwise inside the recirculation zone (e.g., in high-speed vehicles) to act as a controller. The base pressure in the dead zone and the wall pressure along the square duct length have been measured with and without control. Experiments were carried out for nozzle pressure ratios (NPRs) of 2, 3, 6 and 7.8. When the cylinder was rotated clockwise as an active controller, the base pressure was found to increase by as much as 56% in the perfectly expanded case and up to 17% in over expanded flows. This drastic increase in the base pressure is correlated to an equivalent drag reduction. In addition, adding an active control had no negative impact on the main flow field. This is important as any disturbance in the main flow field at high speeds may lead to increased oscillations and vibrations, which if not checked may cause material failures. Rotating the cylinder in the clockwise direction near the wall was found to be very effective for higher NPRs.